Analisis Kesesuaian Perencanaan Infrastruktur Teknologi Informasi dengan Kebutuhan Organisasi - Muhammad Aziz; Dicky Pratama (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
Information technology (IT) infrastructure planning plays a strategic role in supporting organizational performance and achieving business objectives. However, many organizations experience misalignment between IT infrastructure planning and organizational needs, leading to inefficiencies, limited system integration, and suboptimal utilization of IT investments (Maulana, 2024; Njanka et al., 2025). This study aims to analyze the suitability of IT infrastructure planning with organizational needs using a quantitative approach. The research framework integrates the Strategic Alignment Model (SAM), Strategic Alignment Maturity Model (SAMM), and COBIT 2019 governance principles. Data were collected through a structured questionnaire distributed to IT managers and system users. A total of 85 valid responses were analyzed using descriptive statistics and gap analysis. The results indicate that IT infrastructure planning is moderately aligned with organizational needs, particularly in supporting operational activities. Nevertheless, significant gaps were identified in system integration, scalability, and long-term infrastructure planning. These findings highlight the importance of continuous evaluation and governance-based IT planning to enhance alignment and ensure sustainable organizational performance.